Model-free PZC filter-based multi-loop speed controller for servo drives - Lim, Hee Sung; Kim, Seok Kyoon; Lee, Kyo Beum (Journal of Power Electronics, 2024)
This paper derives an advanced multi-loop speed feedback system equipped with model-free pole-zero cancellation (PZC) filters for the position and current measurements of servo drives. The proposed feedback system does not necessitate an exact system model, and it renders the transfer function of each loop in a first-order low-pass filter form by involving active damping terms. Furthermore, the PZC filters output the desired speed and current information for each of the loops along the first-order convergent system, independent of the system model. An experimental platform involving a 500 W brushless DC motor, with a digital signal processor as a controller, validates the practical improvement of the proposed feedback system.
Keywords: Cancellation filters; Feedback systems; Filter; Model free; Multiloop; Order reduction; Performance recovery; Pole zero cancellation; Poles-zeros cancellation; Servo drives; Filter; Order reduction; Performance recovery; Servo drive; Speed control